Stanley's "This is the life!" - Rebein, Alyssa Chase, 1965-; Chase, Andra, 1942- (Kansas City, MO : MarshMedia, 2008)
When Stanley the bear falls asleep in a van he has raided, he winds up living at a drive-in movie theater where he gorges on junk food and gains lots of weight, until finally he realizes that this is no life for a bear and he makes the long trek back to his forest home.
Keywords: Bears -- Fiction; Health -- Fiction; Food habits -- Fiction; Nutrition -- Fiction